1999
DOI: 10.1007/s001980050148
|View full text |Cite
|
Sign up to set email alerts
|

Bone Densitometry: A New, Highly Responsive Region of Interest in the Distal Forearm to Monitor the Effect of Osteoporosis Treatment

Abstract: The bisphosphonates have been introduced as alternatives to hormone replacement therapy (HRT) for the treatment and prevention of postmenopausal osteoporosis. The expected increasing application in at clinical practice demands cost-effective and easily handled methods to monitor the effect on bone. The weak response at the distal forearm during antiresorptive treatment has restricted the use of bone densitometry at this region. We describe a new model for bone densitometry at the distal forearm, by which the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The ultra‐distal radius region has comparable amounts of trabecular bone (65%) to that of the hip or spine, making it an attractive site for bone densitometry [21], and providing precise BMD measurements with a high predictive value for fracture risk. Data from a recent study exploring the prevalence of osteoporosis in men already being treated for prostate cancer with ADT suggested that the BMD of the radius might be preferable to axial osteometry [22].…”
Section: Discussionmentioning
confidence: 99%
“…The ultra‐distal radius region has comparable amounts of trabecular bone (65%) to that of the hip or spine, making it an attractive site for bone densitometry [21], and providing precise BMD measurements with a high predictive value for fracture risk. Data from a recent study exploring the prevalence of osteoporosis in men already being treated for prostate cancer with ADT suggested that the BMD of the radius might be preferable to axial osteometry [22].…”
Section: Discussionmentioning
confidence: 99%
“…This forearm region is affected minimally by degenerative changes compared with the spine. 5 Calcium, 25(OH)-vitamin-D, parathyroid hormone (PTH) and AED levels were measured routinely. Previous and current AED therapy, fractures and wheelchair dependency were ascertained from the medical notes.…”
Section: Bone Mineral Density; Antiepileptic Drugs; Osteoporosismentioning
confidence: 99%
“…Scans for a subset of women in study 1 were reanalyzed to determine BMD in the new region of interest (N-ROI), a region in the ultradistal forearm with a high content of trabecular bone. 8…”
Section: Bone Densitometrymentioning
confidence: 99%